Problems Faced by Pashto Speaking Community in the Articulation of English Fricative Consonants at Undergraduate Level in Swabi (Journal of Social Sciences Review, 2022)
The present research study aims at exploring the phonological errors with regard to the segmental features committed by the Pashtun ESL learners in Swabi (Khyber Pakhtunkhwa). In this research study, the researchers have used an audio recording as a tool to collect the data from the respondents. Both males and females were included in the data collection to fulfil the ethics of the research. The data was analysed and presented in a tabulated form. The results of the research show that Pashto speakers at Distt Swabi are significantly affected by the first language (Pashto) in the speaking of English, especially in terms of pronunciation. It is hoped that the findings of this research will present a set of general ideas to EFL teachers about the possible problems that the Pashto speakers of English in the area may face in pronunciation. Furthermore, English language teachers being aware of these problems of the students, like lack of familiarity with certain phonemes, and lack of concentration, can accommodate these problems by giving more time to focus on the phonemes that are creating a problem.
Keywords: Phonetics; Phonology; ESL Learning; Errors; Pronunciation/Articulation; Consonants; Fricatives